Overview of the Implementation of Medical Record Maintenance at Tarakan Hospital Jakarta in 2021: A Qualitative Study - Noviliana, Tiara; Siswati; Puteri Fannya; Wiwik Viatiningsih (Open Access Indonesian Journal of Medical Reviews, 2022)
A medical record is a file that contains notes and documents about patient identity, examination, treatment, actions, and other services that have been provided to patients. Medical records in carrying out maintenance and protection so that medical records are protected from damage and can facilitate the service process. This study discusses the process or activities of maintaining medical records at the Tarakan Hospital, Jakarta. The purpose of this study was to find out what factors could trigger the occurrence of damage or dangers to the medical record unit and to find out the preventive actions taken by the hospital in protecting medical records. This type of research uses a qualitative descriptive method, which describes the implementation of the maintenance of medical record files in the filing room in 2021. The implementation of medical record maintenance by medical record unit officers, it does not follow the SOP that has been set by Tarakan Hospital Jakarta. Constraints in maintaining medical records are seen from biological, chemical, environmental, and security factors. These obstacles are often the factors that cause damage to medical records such as dust, fire/coal on cigarettes, pests/insects, and chemical liquids and maintenance of medical records at the Tarakan Hospital.